Academic visit by Cut Meutia Pharmaceutical Vocational School, Banda Aceh, Indonesia / Syahida Fathiah Ahmad Kamal and Assoc. Prof. Dr. Mahmathi Karuppannan - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 9th March 2023, Faculty of Pharmacy hosted an academic visit by 10 lecturers and 75 students from Cut Meutia Pharmaceutical Vocational School, Banda Aceh. The visit started with a welcoming session by Dr. Mohd Shahezwan Abd Wahab, the Deputy Dean of Academic Affairs and Dr. Aida Azlina Ali, the Deputy Dean of Student Affairs. In this session, the delegation was introduced to the academic programs, research expertise and services offered at Faculty of Pharmacy and 2 students representing the student council (MPP) were invited to share about the students' activities at the faculty and a brief presentation on safety use of medicines. The session continued with a special traditional dance performance by students of Cut Meutia Pharmaceutical Vocational School. Following that, the delegates visited the facilities available at the faculty such as the Analytical Unit laboratory.